Robust Secure Beamforming and Power Splitting for Millimeter-Wave Cognitive Satellite-Terrestrial Networks With SWIPT - Yan, Yan; Yang, Weiwei; Guo, Daoxing; Li, Shengnan; Niu, Hehao; Zhang, Bangning (IEEE systems journal, 2020)
In this article, we investigate robust secure beamforming and power splitting for multiuser secondary terrestrial networks with simultaneous wireless information and power transfer, which coexist with primary satellite networks in the same millimeter-wave bands. In particular, a base station is equipped with a uniform planar array, and a secondary user (SU) employs a power-splitting-type receiver. Under an angle-based channel state information (CSI) error model, we formulate an optimization problem with the aim to maximize the minimal worst-case achievable secrecy rate among all SUs, while satisfying the quality-of-service (QoS) constraints for each SU, the interference limit for a primary satellite earth station, and the power consumption limit for the base station. To handle the intractable problem, we propose an iterative algorithm based on a series of approximations and a concept of the convex hull. Specifically, the former is for jointly designing secure beamformers and power splitting ratios, and the latter is for ensuring robustness to the angle-based CSI uncertainty. Furthermore, we analyze the computational complexity of this algorithm and extend the proposed scheme for solving a weighted sum secrecy rate maximization problem. Numerical results validate the effectiveness and superiority of the proposed scheme compared to the existing approaches, and obtain an insight into different robust designs.